The First Dorsal Metacarpal Artery Flap Family: A Review - Couceiro, Jose; de Prado, Marta; Menendez, Guillermo; Manteiga, Zaira (The Surgery Journal, 2018)
Deep soft tissue injuries around the thumb can severely hinder hand function if not treated correctly. Many different surgical options have been described for the treatment of these serious lesions, including microsurgical flaps, such as toe to hand flaps, local flaps, and distant pedicled flaps. The first dorsal metacarpal artery family of flaps belongs to this last category. These flaps can be performed in different ways, as a racquet, as an island flap, and as a bilobed flap including the second metacarpal artery, among others.The aim of the following article is to review the basic concepts involved in the use of these flaps in reconstructive hand surgery.
Keywords: first dorsal metacarpal artery; FDMA flap; thumb trauma; thumb recosntruction